Gambaran Tingkat Pengetahuan Masyarakat Tentang Dagusibu Obat Di Dusun Jenetallasa Kecamatan Pallangga Kabupaten Gowa - Santi Elvira; Asty Vebrianti Asjur; Syaifullah Saputro; Tamzil Azizi Musdar; Wahyu Nuraini Hasmar (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Currently, people still often make mistakes when it comes to getting, using, storing and disposing of medicines correctly. This can cause undesirable things to happen in treatment such as drugs that cannot function optimally, drugs that are used incorrectly, drugs that are not stored properly and careless disposal of drugs. These undesirable things can of course be detrimental to people when using drugs. Indonesians are famous for their habit of self-medication, namely taking medicine without a prescription to treat minor illnesses. Self-medication is an option that many people choose. Self-medication, which is the term for self-medication, is one of the steps that people can take to maintain their health. So it is necessary to provide outreach about DAGUSIBU medicine. By providing knowledge about the importance of handling medicines through DAGUSIBU and Gema Cermat, it is hoped that the community in Jenetallasa Hamlet, Pallangga sub-district will get a proper understanding about medicines and drug abuse can be avoided and treatment will be more appropriate in the community. DAGUSIBU is the most important thing because knowledge is one way to be able to use medicine, store, obtain and dispose of medicine according to the DAGUSIBU concept. The knowledge category includes the ability to recall from memory specific and general things, methods and processes or remember a pattern, structure, symptom or event. According to WHO, drug use is said to be rational if the patient receives drugs that suit their clinical needs, in doses according to their needs.